The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1021/jo00158a041
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of 2,6-dimethyl- and 2,4,6-trimethylpyridine with trifluoromethanesulfonic anhydride

Abstract: Reaction of 2,6-Dimethyl-and 2,4,6-Trimethylpyridine with Trifluoromethanesulfonic Anhydride Summary: The reaction of trifluoromethanesulfonic anhydride with 2,6-dimethyl-and 2,4,6-trimethylpyridine produces compounds in which a methyl hydrogen is replaced by either a trifluoromethyl or a [(trifluoromethyl) sulfinyl]oxy group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…It was found that the one‐pot treatment of 71 with three equivalents of DBU at room temperature for 20 min afforded the elimination product 59 , albeit in low yield (22 %). Furthermore, the following three experimental results have been reported (Scheme ): 1) Matsumura reported that 2‐picoline N ‐oxide was transformed with tosyl chloride into 2‐chloromethylpyridine via 2‐tosyloxymethylpyridine;73 2) picoline N ‐oxides reacted with Tf 2 O at −20 °C to give the stable N ‐sulfonyloxy triflate salts;74 and 3) 2,6‐dimethylpyridine reacted with Tf 2 O to afford the compound in which a methyl hydrogen atom was replaced by a [(trifluoromethyl)sulfinyl]oxy group 75. Encouraged by these results, we anticipated that using Tf 2 O instead of TFAA in the Matsumura–Boekelheide rearrangement would more efficiently afford the elimination product 59 .…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the one‐pot treatment of 71 with three equivalents of DBU at room temperature for 20 min afforded the elimination product 59 , albeit in low yield (22 %). Furthermore, the following three experimental results have been reported (Scheme ): 1) Matsumura reported that 2‐picoline N ‐oxide was transformed with tosyl chloride into 2‐chloromethylpyridine via 2‐tosyloxymethylpyridine;73 2) picoline N ‐oxides reacted with Tf 2 O at −20 °C to give the stable N ‐sulfonyloxy triflate salts;74 and 3) 2,6‐dimethylpyridine reacted with Tf 2 O to afford the compound in which a methyl hydrogen atom was replaced by a [(trifluoromethyl)sulfinyl]oxy group 75. Encouraged by these results, we anticipated that using Tf 2 O instead of TFAA in the Matsumura–Boekelheide rearrangement would more efficiently afford the elimination product 59 .…”
Section: Resultsmentioning
confidence: 99%
“…2,6-Lutidine switched the regioselectivity to favour 3a (entry 6), but is known to decompose in the presence of Tf 2 O. 24 The more stable 2,6-di-tert-butylpyridine gave a poor yield. To our suprise, 2,6-difluoropyridine gave reasonable selectivity for 3a (entry 7).…”
Section: Paper Syn Thesismentioning
confidence: 99%
“…Together with C(sp 2 )CF 3 bond‐forming reactions,2–4 there are many examples of reactions to construct a C(sp 3 )CF 3 bond, such as the addition of anionic CF 3 species to carbonyl groups,5 trifluoromethylation at the α‐position of carbonyl compounds,6 addition of a CF 3 radical to alkenes,7 and cross‐coupling reactions 8. However, the examples of C(sp 3 )CF 3 bond‐formation reactions by C(sp 3 )H trifluoromethylation are still rare 9. 10…”
Section: Benzylic Trifluoromethylation Of Six‐membered Heteroaromaticmentioning
confidence: 99%